Implications of Broad Spectrum Antibiotic Treatment in Children with Acute Upper Respiratory Tract infection. A Clinical Study - Kiran Fatima, Muhammad Amir, Shahnaz Bano Memon, Fareeda Islam, Majid Ali Hingoro, Abid Rafiq Chaudhry (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and objectives: The aims and objectives of current study were to identify the proper spectrum of different broad spectrum antibiotics in children for acute upper respiratory infections. Methodology: Total 200 children patients with acute upper respiratory tract infections like acute sinusitis, acute bronchitis, pharyngitis, otitis media, laryngitis, and tracheitis were reported. Different antibiotics such as quinolones, amoxicillin, co-amoxiclav, azithromycin and clarithromycin were prescribed. Results: All individual reported their medical conditions and predominate symptoms were fever, cough, sore throat and wheezing. Broad spectrum antibiotics were prescribed to the all children patients regarding to their culture sensitivity test. These agents, Amoxicillin, Clamoxin, third generation Cephalosporin, Ciprofloxacin, Levofloxacin, Cefixime were given to all children according to their sensitivity spectrum. Conclusion: More incidences of acute upper respiratory infections with empyema being caused by bacteria have been documented. Microorganisms S. pneumonia and H. influenza were found in a large number of samples.